PENILAIAN AUTENTIK BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DAN PENERAPANNYA PADA PENDIDIKAN AGAMA ISLAM - Agus Sriyanta (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2022)
This research aims to describe authentic assessment based on information and technology (IT) and its application in Islamic religious education. Assessment is one of the activities that must be carried out in every learning process, which functions to determine the results of the learning process activities. Efforts must be made to assess all aspects, namely attitudes, skills and knowledge, and avoid assessments that have previously been carried out which tend to assess cognitive aspects, and ignore affective and psychomotor aspects. Authentic assessment is one way of conducting assessments that can be used as an alternative in assessing student learning progress so that comprehensive information is obtained regarding student learning outcomes, interests and needs. Authentic assessment can be combined with traditional assessment. The research method used is descriptive qualitative by describing phenomena and existing literature. The results of the study show that the implementation of learning process assessment using authentic assessment can also be used by teachers as an evaluation of the learning process that has been implemented. In authentic assessment, the teacher's ability to carry out assessments is required to be able to use the assessment format used to evaluate students. Information technology-based assessment from an educational perspective is an assessment process carried out involving media such as computers, LCDs, cellphones, and the like, in order to optimize assessment in learning that is more efficient and interesting.